Physical and electrical breakdown characteristics of oilImpregnated kenaf paper with the introduction of external PVA for transformer application - Muhammad Umair; Azis, Norhafiz; Halis, Rasmina; Jasni, Jasronita (Universiti Putra Malaysia, 2023)
This work examines the physical and electrical breakdown characteristics of kenaf paper coated with Polyvinyl Alcohol (PVA) for application in power transformers. The paper was made from kenaf bast fibers using the soda pulping method, whereby the pulps were subjected to 12,000 beating revolutions. PVA with weight percentage concentration up to 6% was introduced to the beaten kenaf through a spin coating approach. The structure of the kenaf paper was examined through Scanning Electron Microscopy (SEM). The physical properties examined were apparent density, Tensile Index (TI), Burst Index (BI), and Tear Index (TeI), while AC breakdown voltage and strength were analyzed for the electrical property. It is found that the beating and external PVA improve the kenaf paper’s apparent density, TI, BI, and AC breakdown strength while the TeI decreases.